Too poor for peace? global poverty, conflict, and security in the 21st century - Brainard, Lael.; Chollet, Derek H.; ProQuest (Firm) (Washington, D.C. : Brookings Institution Press, 2007)
"Investigates the complex and dynamic relationship between poverty and insecurity, exploring possible agents for change. Brings the latest lessons and intellectual framework to bear in an examination of African leadership, the private sector, and American foreign aid as vehicles for improving economic conditions and security"--Provided by publisher.
The tangled web : the poverty-insecurity nexus / Lael Brainard, Derek Chollet, and Vinca LaFleur -- Poverty breeds insecurity / Susan E. Rice -- Poverty and violence : an overview of recent research and implications for foreign aid / Edward Miguel -- Demography, environment, and civil strife / Colin H. Kahl -- Resource and environmental security / Anthony Nyong -- The demographics of political violence : youth bulges, insecurity, and conflict / Henrik Urdal -- Embracing the margins : working with youth amid war and insecurity / Marc Sommers -- The role of leadership in overcoming poverty and achieving security in Africa / Robert I. Rotberg -- Operating in insecure environments / Jane Nelson -- Breaking the poverty-insecurity nexus : is democracy the answer? / Jennifer L. Windsor.
"The chapters draw from a conference at the Aspen Institute held on August 2 to August 4, 2006, called, "The Tangled Web: The Poverty-Insecurity Nexus" --P. viii.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Poverty -- Developing countries -- Congresses; Political violence -- Developing countries -- Congresses; Economic assistance, American -- Developing countries -- Congresses; Public-private sector cooperation -- Congresses; Peace-building -- Congresses; Electronic books